Nelson's Trafalgar the battle that changed the world - Adkins, Roy 1951- (Viking, 2005)
On October 21, 1805, as Britain's Royal Navy under the command of Horatio Nelson clashed with Napoleon's forces in an epic sea battle off the coast of Spain, the fate of Europe hung in the balance. Though the cost was high--and Nelson himself was killed--the British victory prevented Napoleon from invading Britain and paved the way for the eventual defeat of the French emperor. Without Trafalgar there would have been no Waterloo. The Battle of Trafalgar set Britain on its vast imperial course. Now, on the battle's 200th anniversary, Roy Adkins offers readers a brutally vivid, gunport-level account. Capturing the harsh conditions in which sailors lived and died, the mechanics of nautical warfare, and the relentless violence of 19th century naval combat, this book will be appreciated by fans of military history and Patrick O'Brian.--From publisher description.
First published under the title: Trafalgar: the biography of a battle. London : Little, Brown, 2004.
Includes bibliographical references (p. [375]-380) and index
Keywords: Nelson, Horatio <Viscount, 1758-1805> - Leadership militaire; Nelson, Horatio Nelson -- Viscount -- 1758-1805 -- Military leadership; Nelson, Horatio -- 1758-1805; Großbritannien -- Navy; Geschichte 1800-1900; Guerres napoléoniennes, 1800-1815; Trafalgar, Bataille de, 1805; Trafalgar, Battle of, 1805; Napoleonic Wars, 1800-1815; Seeschlacht bei Trafalgar; France - Histoire navale - 19e siècle; Grande-Bretagne - Histoire navale - 19e siècle; Frankreich; Großbritannien; Great Britain -- History, Naval -- 19th century; France -- History, Naval -- 19th century